Soyasapogenol B Attenuates Laryngeal Carcinoma Progression through Inducing Apoptotic and Autophagic Cell Death. Issue 7 (18th October 2019) - Zhi, Lili; Song, Daoliang; Ma, Liji; Feng, Tao
ABSTRACT: Soyasapogenol B (Soy B), a constituent of soybean, has been shown to exhibit antitumor activities against different types of cancers. However, to our knowledge, no studies so far have investigated the effect of Soy B in human laryngeal carcinoma. This study, therefore, aimed to determine the effect of Soy B in human laryngeal carcinoma cell lines HeP‐2 and TU212 and to elucidate the possible underlying mechanisms by which Soy B can induce its antitumor effects. The results showed that Soy B effectively attenuated the cell growth by causing G0/G1 phase cell cycle arrest in laryngeal carcinoma cell lines. Moreover, the percentage of apoptotic and autophagic cells dramatically increased upon exposure to Soy B. Western blotting results confirmed that Soy B can alter the expression levels of established markers of apoptosis and autophagy. Interestingly, both apoptosis inhibitor (ZVAD‐fmk) and autophagy inhibitor (3‐MA) could partially reverse the effect of Soy B, while blocking autophagy did not cause obvious alteration in the percentage of apoptotic cells. Similarly, in vivo studies validated that Soy B could effectively reduce the size of the tumor and induce apoptosis and autophagy in tumor tissues. Collectively, these results suggested that Soy B can exert anticancer activities against laryngeal carcinoma through inducing apoptotic and autophagic cell death. Our study highlighted the potential role of Soy B as a chemotherapeutic agent for laryngeal carcinoma. Anat Rec, 2019. © 2019 American Association for Anatomy Anat Rec, 303:1851–1858, 2020. © 2019 American Association for Anatomy